Complications in deep anterior lamellar keratoplasty – A retrospective cross sectional interventional analysis in a large series - Shreesha Kumar Kodavoor; Neha Rathi; Ramamurthy Dandapani (Oman Journal of Ophthalmology, 2023)
AIM: To analyse complications in patients managed with deep anterior lamellar keratoplasty (DALK) for diseases of anterior corneal stroma. MATERIALS AND METHODS: This was a retrospective analysis of all the patients who underwent DALK in a tertiary care center in South India from 2010 to 2021. A total of 484 eyes in 378 patients were included in the study. Patients who underwent DALK for advanced keratoconus, keratoconus with Bowman's membrane scar, healed hydrops, macular corneal opacity, macular corneal dystrophy, granular corneal dystrophy, spheroidal degeneration, pellucid marginal degeneration, post-LASIK ectasia, descemetocele, postcollagen cross-linking aborted melt and dense scar, and postradial keratotomy were included in the study. The patients were followed up for 17.6±9.4 months(1–10years). RESULTS: Complications noted in the surgery were intraoperatively Descemet's membrane perforation in 32 eyes (6.6%), postoperatively secondary glaucoma in 16 eyes (3.31%), cataract in 7 eyes (1.45%), suture-related complications in 5 eyes (1.03%), graft rejection in 3 eyes (0.61%), traumatic dehiscence in 2 eyes (0.41%), filamentary keratitis in 2 eyes (0.41%), interface infiltrate in 1 eye (0.21%), and recurrence of disease in 4 eyes (8.77%) out of 57 eyes with corneal dystrophy. CONCLUSION: DALK as an alternative to penetrating keratoplasty for anterior corneal stromal diseases has proven to be better time and again. It has become an automatic choice for diseases of anterior cornea requiring keratoplasty. Complications occurring at any stage of surgery can be identified and managed effectively resulting in optimal outcome. This article compiles complications post DALK.